The Phenomenon of Child Marriage after the Enactment of Law No. 16 of 2019 from the Perspective of Islamic Family Law - Endang Sudarman; Muhil Mubarok (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Marriage is intended to create a harmonious and loving family, but early marriage, defined as marriage below the legal age set by Indonesian law, often involves children aged 0-18 and is therefore categorized as child marriage. This study aims to examines the phenomenon of child marriage after the enactment of Law No. 16 of 2019 and analyzes it from the perspective of Islamic Family Law. The study employs a library-based approach, with data collected, analyzed, and organized from articles, books, and previous studies. The study highlight that the practice of child marriage engenders severe repercussions across multiple dimensions. Developmentally, it curtails the opportunity for married children to achieve physical and psychological growth. Educationally, it abrogates their fundamental right to schooling. Socially, it renders them disproportionately vulnerable to sexual violence. Medically, early pregnancy, a common outcome, exacerbates maternal mortality rates and correlates with a heightened prevalence of infant growth disorders and malnutrition. Within the Indonesian context, child marriage constitutes a grave and pervasive issue. Under the legal regime predating the amendment of Law Number 1 of 1974 on Marriage which prescribed 16 years for women and 19 years for men as the minimum age for matrimony the incidence of such unions was substantially elevated. Statistical evidence reveals that approximately 375 girls, representing one in every nine, enter into marriage prior to attaining 18 years of age each day.